Analgesic and Antidepressant Effects of the Clinical Glutamate Modulators Acetyl-L-Carnitine and Ketamine - Freo, Ulderico; Brugnatelli, Viola; Turco, Fabio; Zanette, Gastone (Frontiers in Neuroscience, 2021)
Pain and depression are leading cause of disability and of profound social and economic burden. Their impact is aggravated by their chronicity and comorbidity and the insufficient efficacy of current treatments. Morphological and functional metabolism studies link chronic pain and depressive disorders to dysfunctional neuroplastic changes in fronto-lymbic brain regions that control emotional responses to painful injuries and stressful events. Glutamate modulators are emerging new therapies targeting dysfunctional brain areas implicated in the generation and maintenance of chronic pain and depression. Here, we report the effects of two clinically approved glutamate modulators: acetyl-L-carnitine (ALCAR) and S,R(±)ketamine (KET). ALCAR is a natural neurotrophic compound currently marketed for the treatment of neuropathies. KET is the prototypical non-competitive, antagonist at N-methyl-D-aspartate glutamate receptors, and a clinically approved anesthetic. Although they differ in pharmacological profiles, ALCAR and KET both modulate aminergic and glutamatergic neurotransmissions, and pain and mood. We assessed in rats the effects of ALCAR and KET on cerebral metabolic rates for glucose (rCMRglc), and assessed clinically the effects of ALCAR in chronic pain and of KET in postoperative pain. ALCAR and KET increased rCMRglc at similar degrees in prefrontal, somatosensory and cingulate cortices and KET increased rCMRglc at a different, much larger degree in limbic and dopaminergic areas. While rCMRglc increases in prefrontal cortical areas have been associated to analgesic and antidepressant effects of ALCAR and KET, the marked metabolic increases KET induces in limbic and dopaminergic areas have been related to its psychotomimetic and abuse properties. In patients with chronic neuropathic pain, ALCAR (1000 mg/day) yielded to a fast (two weeks) improvement of mood and then of pain and quality of life. In day-surgery patients, KET improved dischargeability and satisfaction. In obese patients undergoing bariatric surgery, a single, low-dose of KET (0,5 mg/kg) at induction of anesthesia determined a very fast (hours) amelioration of postoperative depression and pain, and an opioid-sparing effect. These findings indicate that ALCAR and KET, two non-selective glutamate modulators, still offer viable therapeutic options in comorbid pain and depression.